2011
DOI: 10.1007/s10646-011-0730-1
|View full text |Cite
|
Sign up to set email alerts
|

Mercury exposure and neurochemical impacts in bald eagles across several Great Lakes states

Abstract: In this study, we assessed mercury (Hg) exposure in several tissues (brain, liver, and breast and primary feathers) in bald eagles (Haliaeetus leucocephalus) collected from across five Great Lakes states (Iowa, Michigan, Minnesota, Ohio, and Wisconsin) between 2002-2010, and assessed relationships between brain Hg and neurochemical receptors (NMDA and GABA(A)) and enzymes (glutamine synthetase (GS) and glutamic acid decarboxylase (GAD)). Brain total Hg (THg) levels (dry weight basis) averaged 2.80 μg/g (range:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 42 publications
5
50
0
Order By: Relevance
“…For most contaminants there were several instances of samples with very high levels which may indicate that some Bald Eagles in our study area were being exposed to potentially toxic levels of contaminants. This is consistent with other studies on Bald Eagles in the Midwest that have documented elevated levels of contaminants such as lead and mercury in blood and tissue samples (Rutkiewicz et al 2011, Nam et al 2012, Warner et al 2014.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For most contaminants there were several instances of samples with very high levels which may indicate that some Bald Eagles in our study area were being exposed to potentially toxic levels of contaminants. This is consistent with other studies on Bald Eagles in the Midwest that have documented elevated levels of contaminants such as lead and mercury in blood and tissue samples (Rutkiewicz et al 2011, Nam et al 2012, Warner et al 2014.…”
Section: Discussionsupporting
confidence: 92%
“…Following a ban on the use of DDT in 1972, complemented by conservation and recovery efforts, the Bald Eagle has undergone a spectacular recovery across much of its range including Iowa (Shepherd 2013). However, there are concerns about exposure of Bald Eagles to environmental contaminants, particularly lead and mercury (Rutkiewicz et al 2011, Haig et al 2014. The ingestion of spent lead ammunition, lead fragments embedded in food items, and lead fishing tackle has been linked to morbidity and mortality in several avian species including Bald Eagles (Fisher et al 2006, Cade 2007, Bedrosian et al 2012.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the interaction o f MeHg or inorganic Hg (iHg, Hg2+) with cysteine residues may inhibit, stimulate or damage components o f the dopaminergic (Gomes et al, 1976), cholinergic (Castoldi et al, 1996), GABAergic (Huang and Narahashi, 1997;Narahashi et al, 1994), and glutamatergic (Albrecht and Matyja, 1996) signaling pathways. In wildlife studies, MeHg exposure was associated with significant reductions in y-aminobutyric acid type A receptor (GABAa-R) binding in lab-exposed mink (Mustela vison) and decreased N-methyl-D-aspartate receptor (NMDA-R) binding in several brain regions of MeHg-exposed bald eagles (Haliaeetus leucocephalus) (Rutkiewicz et al, 2011;Scheuhammer et al, 2008), mink (Basu et al, 2007c), and polar bears ( Ursus maritimus) (Basu et al, 2009). It is believed that such MeHg-associated neurochemical changes may have consequences to the whole organism as these receptors are components o f the main inhibitory and excitiatory pathways in the central nervous system, and they play important roles in animal behaviour, memory and motor function (Popescu, 2005;Reis et al, 2009;Vicini and Ortinski, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations o f MeHg below ~ 2-5 mg kg"1 ww were likely below thresholds o f overt MeHg intoxication in mink (Suzuki, 1979;Wobeser et al, 1976). However, HgT concentrations measured in the central nervous system (CNS) o f Arctic beluga whales exceeded concentrations associated with neurochemical variation in wildlife and avian studies (Basu et al, 2005c;Basu et al, 2007b;Basu et al, 2007c;Basu et al, 2009;Basu et al, 2005e;Rutkiewicz et al, 2011;Scheuhammer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%